Selected practical and methodological aspects of renovations and adaptations of modernist buildings from the after-war period in Upper Silesia = Wybrane aspekty praktyczne i metodologiczne renowacji i adaptacji obiektów modernistycznych z lat powojennych na terenie Górnego Śląska - Wagner, Tomasz; Nakonieczny, Ryszard (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the beginning of the economic transformation in Poland, buildings constructed after 1945 were treated as symbols of an unacceptable system. Currently, the modernist architecture of the twentieth century is seen as an important element of historical and cultural heritage. However, the problem of its protection against a number of adverse events that may lead to the loss of its essential values and often result in its destruction has been recently growing.
Keywords: obiekty modernistyczne; architektura modernistyczna; Śląsk, Górny; adaptacja; renowacja obiektów; modernist buildings; modernist architecture; Upper Silesia; renovation; adaptation